Mathematical modelling of an electrostatic oiling machine for steel strips. Issue 1 (31st December 2023) - Landauer, Julian; Kugi, Andreas; Steinböck, Andreas
ABSTRACT: This paper deals with the mathematical modelling of the electrostatic spraying process in an industrial electrostatic oiling machine (EOM) for steel strips. Measurements from an industrial EOM show that the thickness and inhomogeneity of the oil film on the strips frequently exceed specified tolerance limits whereby the reasons were previously unknown. A numerical model of the spraying process is developed in ANSYS Fluent, which serves as the basis for a root-cause analysis of the erroneous oil film thickness. In contrast to other works in this area, a droplet break-up model, which describes the break-up of the oil droplets due to the charge they carry, is included to get more accurate results. The model is validated based on measurement data from an industrial oiling machine. It is demonstrated that the model yields a better understanding of the spraying process and it is successfully used to improve the oiling process.